Model-model Tanggung Jawab Sosial dan Aspek Perpajakannya - Irawan, Ronny (Jurnal Akuntansi Kontemporer, 2009)
Corporate social responsibility is contra-service of company to its environment and society since company already has gains from them. There are various models of Corporate Social Responsibility carried out by the companies in Indonesia. They can involve directly to perform the events of responsibility through third party. They can also make a cooperation with another party or join to another party. They can give contributions to the people and their environment directly by increasing their quality of life. But they have to obey the rules and regulations set by government for their sustainability. The different types of social responsibility programs need different treatments of their taxation.